A study of the definitions of mathematical concepts in first year mathematics textbook used in Our Lady of Penafrancia Seminary - Valdemoro, Filomeno Laurio 1933- (1974)
An analysis of the definitions of mathematical concepts, in the book "Exploring Modern Mathematics" by Keedy, Jameson and Johnson is made in this study by using an evolved criteria for analysis. The set of criteria consists of: a definition of the term "definition", its classification, and the characteristics of a good definition in mathematics.
Thesis (M.A.T.Elementary Mathematics)--University of the Philippines
Keywords: Mathematics -- Terminology